2022
DOI: 10.3390/smartcities5040077
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Stakeholder Acceptance of a Malaysian Smart City

Abstract: Smart city technology is only considered in some cities depending on the resident requirements, whereas smart initiatives are adopted easily in others. One of the first critical steps toward understanding these aspects of Malaysian smart cities is to empirically study the citizens’ and government agencies’ aspirations to use smart city services. A Malaysia Smart Cities Stakeholders Adoption Model (MSCSA) as a case study based on the unified theory of acceptance and use of technology (UTAUT2) is being developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 114 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…3 [45] suggested that the smart city concept in urban planning aspects needs to be taken crucially. In his seminal article, [23], at this time, municipalities must provide smart city services because they are essential to society and are necessary for municipalities to perform their essential functions. Then, it is anticipated that smart cities will increase these capabilities by integrating more closely with the community and its residents.…”
Section: Urban Planning Contemplates Smart Citymentioning
confidence: 99%
See 1 more Smart Citation
“…3 [45] suggested that the smart city concept in urban planning aspects needs to be taken crucially. In his seminal article, [23], at this time, municipalities must provide smart city services because they are essential to society and are necessary for municipalities to perform their essential functions. Then, it is anticipated that smart cities will increase these capabilities by integrating more closely with the community and its residents.…”
Section: Urban Planning Contemplates Smart Citymentioning
confidence: 99%
“…Several of Malaysia's Smart City policies are shown in Table 1. The Smart City's component that links directly to urban planning aspects technically can be seen in the implementation of (1)Smart Mobility which are transportation, movement, traffic management, and so forth, (2)Smart Economy which is the industrial park or commercial area focuses, (3) Smart Environment which is waste management, low-carbon, green building and so forth, (4) Smart People which are communities participatory in the planning process like Seranta(Public Hearing ), ( 5) Smart Government which are e-government and (6) Smart Digital Infrastructure which are Wifi, Highspeed Internet, 5G and so forth [23]. • Smart Governance…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the last two decades, most countries have implemented electronic government systems to deliver public services and support citizens' participation during public decision making under the United Nations Development Programs and using their methods. Even though some countries have failed to adopt digital transformation, smart or e-government enables citizens to participate in social, economic, political, and administrative decisions to create a sustainable government [3]. Citizen participation in urban development matters and vital national events is the most crucial factor in innovative governance, so that people can express their wishes, needs, demands, and voices in city development and their choice of government leaders [4].…”
Section: Introductionmentioning
confidence: 99%
“…So, throughout history, as we have seen, the way people will live in a country under a 17 government has been influenced by different factors like Economics, Social, Culture, Environment, and Technology, and right now, the most crucial factor in the present is Technology. That is why countries need to evolve for the future with the help of Technology [25] and adapt and mold their governance practices according to Technological advancement and; how it should be done, we will discuss this in the next section.…”
Section: Introduction 1backgroundmentioning
confidence: 99%